Diagnóstico de los procesos administrativos en el cumplimiento de los objetivos de las instituciones de Educación Básica de la prarroquia Canchagua, cantón Saquisilí. Propuesta de un manual de procedimiento período 2013-2014. - Palacios Mina, Azucena Verónica (2015)
The educational institutions provide services that look in order to satisfy the necessities and students’ requirements, but the global growth competition has led to higher expectations of students and their families with regardless of educational services of a higher and standardized quality. This development purpose is to design a Manual of Procedures for administrative management according to the necessities of the Educational Institutions of the Canchagua Parish that will provide effectiveness in the application of administrative processes. In the diagnosis, they noticed a series of aspects that negatively impacted the administrative of objectives the non-application of the modern educational administration procedures, and the absence of written norms that define and specify with clarity how and whom should carry out each one of the administrative functions in an effective way. It will be necessary to take the opportunity to make crucial decisions for their institutional development. This work is framed inside a field of investigation of descriptive characters and it´s formulated as a development project whose results will be of a diagnostic type. The population was conformed by authorities, and educational, administrative, and services staff. This hypothesis tested that 60% of the respondents do not know and apply the administrative processes to optimize the objectives, for this reason, it is necessary the use of a Manual of Process. For the collection of data, one will use a survey technique and utilize the questionnaire. The proposal is designed to facilitate the member educational interactions in institutions and its aspirations for the sake of strengthening commitments so that the application of the procedure manual is functional and feasible. The beneficiaries will be the Educational Communities of the Canchagua Parish, who will profit from the strengthening of the educational institutions in the administrative environment, in a way that allows them to seriously confront and appropriately take the decision making process with deep responsibility, in order to be a pioneer in administrative change and to be efficient as possible in receiving the public's general attention